Credit Distribution as a Mediation of Loan to Deposit Ratio, Operational Costs on Operational Income and Non Performance Loan to Return on Asset - hary wijayanto, yudha; Muawanah, Umi; Endah Aprilia, Mitha (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This research study aims to analyze the effect of: (1) LDR on ROA, (2) BOPO on ROA, (3) NPL on ROA, (4) Lending on ROA, (5) LDR on Lending, (6) BOPO on Lending, (7) NPL on Lending, (8) LDR on ROA through Lending, (9) BOPO to ROA through Lending, (10) NPL to ROA through Lending. Using quantitative research, a population of 129 banks in the period and purposive sampling technique. The results of this study prove that LDR has a significant positive effect on ROA so that the hypothesis is accepted; BOPO has a significant negative effect on ROA so that the hypothesis is accepted; NPL has no effect on ROA so that the hypothesis is rejected; lending has a significant positive effect on ROA so that the hypothesis is accepted; LDR has no effect on lending so that the hypothesis is rejected; BOPO has a significant positive effect on lending, so the hypothesis is accepted; NPL has a significant negative effect on lending, so the hypothesis is accepted; lending is unable to mediate the effect of LDR on ROA, so the hypothesis is accepted; lending is able to mediate the effect of BOPO on ROA, so the hypothesis is accepted; and lending is unable to mediate the effect of NPL on ROA, so the hypothesis is accepted.